Understanding Aboriginal Learning Ideology Through Storywork with Elders - Atleo, Marlene R. (Alberta Journal of Educational Research, 2010)
Five Nuu-chah-nulth Elders engaged in the examination of a Nuu-chah-nulth story for what they considered learning. A network of eight learning archetypes inhabited the story to demonstrate a range of learning strategies. The Elders identified features central to a cultural learning project, which included prenatal care and grandparent teaching, spiritual bathing, partnerships, ritual sites, and ancestor names. Learning strategies were understood as embedded and embodied in the form of characters displaying the archetypes. The storywork process used by the Elders, systematized as phenomenological orienteering and operationalized as metaphorical mapping, was found to be a useful methodology.